Importancia del gobierno corporativo y estructura de capital en las empresas listadas en la Bolsa de Valores de Lima. Caso Alicorp - Lizarzaburu B., Edmundo R. (2023)
Corporate Governance is a tool to establish a balance between internal and external stakeholders (Torre, 2005). This document aims to share the conventions regarding corporate governance and interest groups, those that may be useful in the Peruvian context, as well as the impact of the application of good corporate governance practices on, besides the environment, profitability and organization benefits. In this sense, we propose that the correct management in the application of Corporate Governance will improve the performance of the company. The research will first present a theoretical framework on corporate governance and interest groups, followed by the study case carried out on the company Alicorp S.A.A. which contains, first, a description of the macroeconomic and domestic environment, followed by the analysis of Corporate Governance practices, stakeholder management and, briefly, the economic-financial performance of the 2010-2015 period.